2010
DOI: 10.1152/ajpheart.00168.2010
|View full text |Cite
|
Sign up to set email alerts
|

Delayed activation of caspase-independent apoptosis during heart failure in transgenic mice overexpressing caspase inhibitor CrmA

Abstract: Although caspase activation is generally thought to be necessary to induce apoptosis, recent evidence suggests that apoptosis can be activated in the setting of caspase inhibition. In this study, we tested the hypothesis that caspase-independent apoptotic pathways contribute to the development of heart failure in the absence of caspase activation. Acute cardiomyopathy was induced using a single dose of doxorubicin (Dox, 20 mg/kg) injected into male wild-type (WT) and transgenic (Tg) mice with a cardiac-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…We further note that other proteases [27,28], metabolic dysfunction or autophagocytic processes [13] may also play a role in regulating cardiomyocyte demise, specifically when canonical caspase activation is blocked or initial injury is too severe [15].…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedmentioning
confidence: 88%
“…We further note that other proteases [27,28], metabolic dysfunction or autophagocytic processes [13] may also play a role in regulating cardiomyocyte demise, specifically when canonical caspase activation is blocked or initial injury is too severe [15].…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedmentioning
confidence: 88%
“…Cardiac function was evaluated by measuring the left ventricular (LV) pressure-volume (PV) loop to calculate hemodynamic parameters, including cardiac output (CO), stroke work (SW), stroke volume (SV), and isovolumetric relaxation as described previously (3,13).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas some studies have shown that direct caspase inhibition reduces the acute loss of myocardium in various animal models, other studies indicate that caspase inhibition might not be able to completely inhibit apoptosis, likely because apoptosis can be induced in the ischemic-hypoxic injured heart lacking caspase activation by caspaseindependent pathways (63). Nevertheless, regarding alternative potential antiapoptotic therapies indirectly related to caspase inhibition for which some proof of principle exists, it is worth considering that UCF-101 (a small-molecule inhibitor of the mitochondrial Omi/HtrA2 serine protease released into the cytoplasm during induction of apoptosis, that in turn promotes caspase activation) rescues cardiomyocytes and restores LV dysfunction after ischemia/reperfusion injury in the rat heart (64).…”
Section: Cardiomyocyte Deathmentioning
confidence: 99%